Application of Peer Method Tutoring in Cultivating Sense of Belonging Junior High School Students to Online Learning - Butar-Butar, Clara Irmawati; Listiani, Tanti (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
A sense of belonging is a very important feeling for students to build relationships in the classroom community through face-to-face and online learning. The fact that the teacher found during the teaching practice of grade VII junior high school students in online learning, the teacher found a lack of belonging to their class community. Following up on these problems, the teacher facilitates students by applying the peer tutoring method that allows students to get support from teachers and peers so that it has the potential to foster a sense of belonging to students. The purpose of writing is to describe the application of the peer tutor method as an effort to foster a sense of belonging to students, especially in class VII junior high school students. The method used is descriptive qualitative. This research was conducted in SKK Erenos where a total of 52 students became respondents. Writing concludes that the application of the peer tutoring method is carried out by combining synchronous and asynchronous learning to help students foster a sense of belonging in online learning even though they have not achieved maximum results. Teachers need a correct and reflective heart response to face various challenges in the world of education. Teachers cannot change students' personalities but can become facilitators to create class communities that love one another. The advice to the teacher is to continue the implementation of the peer tutoring method consistently for a long time to foster a sense of belonging to students in online learning.